Coastwide Stock Structure of Winter Flounder Using Nuclear DNA Analyses. Issue 1 (6th January 2014) - Wirgin, Isaac; Maceda, Lorraine; Grunwald, Cheryl; Roy, Nirmal K.; Waldman, John R.
Abstract: Many Winter Flounder Pseudopleuronectes americanus populations have declined dramatically. In U.S. waters, Winter Flounder are managed as three stocks: Gulf of Maine, southern New England–Mid‐Atlantic Bight, and Georges Bank. Historically, it was believed that the spawning of inshore stocks occurs exclusively within natal estuaries. Based on the supposition of estuary‐specific spawning, we hypothesized that Winter Flounder exhibit greater stock structure than predicted by the three‐stock model and, in fact, that they exhibit genetic differentiation at the level of individual estuaries. We tested this hypothesis by conducting microsatellite DNA analysis at 12 loci and single‐nucleotide polymorphism analysis at 4 loci on young‐of‐the year and adult Winter Flounder collected from 27 estuaries from Newfoundland to Delaware as well as from Georges Bank. We found highly significant coastwide genetic stock structure among Winter Flounder; however, there was little evidence of estuary‐specific structure. Pooled collections from north and south of Cape Cod were genetically distinct, as were many individual collections compared between these two regions. However, there was little genetic heterogeneity among estuarine collections within either of these major geographic regions. The two Canadian collections from the Miramichi River and Newfoundland were genetically distinct from those in the Gulf of Maine. Our collection from Georges Bank was marginally distinct from the inshore collections from north and south of Cape Cod. Overall, our genetic results support the three‐stock model used to manage Winter Flounder in U.S. waters and indicate the presence of at least two genetic stocks in Canadian waters (the Miramichi River in the Gulf of St. Lawrence and Passamaquoddy Bay in the Bay of Fundy). Furthermore, our data suggest that the spawning of Winter Flounder in nearshore coastal waters is more extensive than previously thought or that homing is weaker, contributing to the absence of genetic differentiation among populations from proximal estuaries.